Evaluation of Soluble Non-Essential Trace Metalsin Shatt Al-Hilla, Iraq - M. AL-TAEE, MAYSON; N. AL-KHATEEB, AHMED; H. HUSSEIN, FALAH; M. ABID, FADHIL (Asian Journal of Chemistry, 2010)
In this study, the levels of non-essential trace elements, namely, aluminium, cadmium, lead and mercury, have been estimated in six different stations along Shatt AI-Hilla river in Babylon Governorate, Iraq. The findings provide baseline data on non-essential trace metal levels in Shatt AI-Hilla river water. The investigation has been monthly accomplished in six stations in Hilla city, Babylon Governorate, for the period between the 1st of November 2001 and the 31st of September 2002. The concentrations of the studied elements have been measured by using atomic absorption instrument type Shimadzu AA-670/gu-7 flame atomic absorption spectrophotometer and flameless graphite furnace. The concentrations of the elements, during the investigation period, were found to be in the ranges 434 ± 780,114 ± 236,36 ± 2 and 75 ± 39 μgL-1 respectively. Comparing these results with the WHO guidelines for the domestic waters revealed that the concentrations of the elements under investigation were within the elevated values. These findings demonstrate that waste materials have been got rid of into the Shatt Al-Hilla river, by human and/or industrial activities, leading to the contamination of the river. Also, a comparison with the previous studies on the river disclosed a decline in the Hg concentration. However, comparing this Hg concentration with that for other locations in Hilla city showed that the concentration falls within the high levels.